미세 가공 기술을 이용한 비행 시간 질량 분석기에 대한 연구 - 윤현중 (The Graduate School, Ajou University, 2007)
This thesis presents the micromachined time-of-flight mass spectrometer (TOFMS). The mass spectrometer uses the difference in mass-to-charge ratio (m/e) of ionized atoms or molecules to separate them from each other. It consists of an ion source that generates ions from the sample, an analyzer that separates the ions according to their m/e values, and a detector that gives the intensity of the ion current for each species. First, the hot-filament ion source and separator of the micro TOFMS have been fabricated by micromachining. The size and the power of the TOFMS have been reduced compared to the conventional TOFMS. Through the characteristic test of a tungsten filament, the emission of the hot electrons from the tungsten filament has been identified. The test of the gas molecule ionization by the hot electron emission has been performed. To find out the optimal voltage, the micro TOFMS with a laser hole for ionization has been fabricated and tested. The electrode voltages adequate for the ion separation have been determined. It is hard to fabricate a tungsten filament since the tungsten filament floating over the silicon substrate is very weak and breakable after making a cavity by the silicon etching technique. As the other hot-filament ion source, a micro ion source with a nickel filament is presented. The proposed micro ion source with a nickel filament has good merits such as inoxidizable characteristic and simple fabrication. To make a space around the filament, the simple nickel filament by electroplating method is fabricated. It is easy to make the filament and it is not easily broken. It has been confirmed that the fabricated ion separator is feasible for the micro TOFMS and the mass spectrum analysis with the micro TOFMS can be accomplished in several seconds. Second, the field emitter ion sources with a carbon nanostructure are presented. The carbon nanoparticle structure is used by the field emitter ion source to get high ionization energy. The diode field emitter and the triode field emitter have been fabricated and their characteristics have been evaluated. The electron current of the diode field emitter is 73.2 μA when the anode voltage is 1100 V. That of the triode field emitter is 3.4 pA when the anode voltage is 1000 V. We also have successfully fabricated the field emitter ion source with carbon nanoparticles. The carbon nanoparticle layer is grown by hot-filament chemical vapor deposition (HFCVD). The carbon nanoparticle field emitter has the triode structure with which we can control the emission current at low voltage. The emission current of the field emission ion source can be controlled from 0 to 18.5 μA when the gate voltage varies from 0 to 175 V. Finally, the fabrication of the microchannel plate detector by anodic aluminum oxide is proposed. MCP detector is widely used for the measurement of the small current. Anodic aluminum oxide is promising material for MCP production since it is possible to fabricate holes of 20~300 nm size. The anodic aluminum oxide structure with a high aspect ratio is obtained by the two step anodization. In the near future, we will have characteristic tests for the MCP detector by aluminum anodization and constitute a micro mass spectrometer with an ion source, an ion separator and a MCP detector on the silicon substrate.
학위논문(박사)----아주대학교 일반대학원 :전자공학과,2007. 8
Keywords: micro mass spectrometer; ion source